The Influence of The Social Environment on Interest in Sports Among High School Students in Makassar - Jarir, Andi Sahrul; Irawati, Andi Febi (Pinisi Journal of Sociology Education Review, 2026)
Interest in sports among adolescents is a key factor in encouraging participation in physical activity, which contributes to students’ health and development. However, the level of interest in sports among high school students is still influenced by various factors, one of which is the social environment. This study aims to analyze the influence of the social environment on interest in sports among high school students in Makassar City. The study population consisted of high school students in Makassar City, with a sample size of 120 respondents selected using purposive sampling. The data collection instrument utilized a questionnaire with a 1–5 Likert scale comprising 30 items, including 15 items for the social environment variable and 15 items for the interest in sports variable. The results of simple linear regression analysis showed an R value of 0.648 with a coefficient of determination (R Square) of 0.420, indicating that the social environment explains 42% of the variation in students’ interest in sports. The regression coefficient for the social environment variable was B = 0.708 with a t-value of 9.26 and a significance level of p = 0.000 (<0.05). These results indicate that the social environment has a positive and significant influence on sports interest among high school students in Makassar City.